2015
DOI: 10.2139/ssrn.2710577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kriging-Based Methods for Simulation Optimization with Heterogeneous Noise

Abstract: a b s t r a c tIn this article we investigate the unconstrained optimization (minimization) of the performance of a system that is modeled through a discrete-event simulation. In recent years, several algorithms have been proposed which extend the traditional Kriging-based simulation optimization algorithms (assuming deterministic outputs) to problems with noise. Our objective in this paper is to compare the relative performance of a number of these algorithms on a set of well-known analytical test functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(70 reference statements)
2
3
0
Order By: Relevance
“…Our analysis is driven by the primal effect of noise on contour-finding algorithms. This effect was already documented in related studies, such as that of Jalali et al [19] who observed the strong impact of (•) on performance of Bayesian optimization. Consequently, specialized metamodeling frameworks and acquisition functions are needed that can best handle the stochasticity for the given loss specification.…”
Section: Summary Of Contributionssupporting
confidence: 67%
See 2 more Smart Citations
“…Our analysis is driven by the primal effect of noise on contour-finding algorithms. This effect was already documented in related studies, such as that of Jalali et al [19] who observed the strong impact of (•) on performance of Bayesian optimization. Consequently, specialized metamodeling frameworks and acquisition functions are needed that can best handle the stochasticity for the given loss specification.…”
Section: Summary Of Contributionssupporting
confidence: 67%
“…The main goal of this article is to present a comprehensive assessment of GP-based surrogates for stochastic contour-finding. In that sense, our analysis complements the work of Picheny et al [31] and Jalali et al [19], who benchmarked GP metamodels for Bayesian optimization where the objective is to evaluate max x f (x).…”
Section: Summary Of Contributionssupporting
confidence: 54%
See 1 more Smart Citation
“…An R package for implementing several of these choices is available in DiceOptim (Picheny et al (2016); Picheny and Ginsbourger (2014)). Jalali et al (2017) also do a similar comparison for heteroscedastic noise.…”
Section: Optimizationmentioning
confidence: 84%
“…Alternative criteria to EI, specifically designed for stochastic problems, also exist within the same framework. Jalali et al (2016) provide a brief summary of some alternative criteria, as well as an in depth comparison between them. An R package for implementing several stochastic optimization methods (including some choices for the replacements of y max ), using the homGP model from Section 3.1, is available in (DiceOptim; Picheny et al (2016); Picheny and Ginsbourger (2014)).…”
Section: Optimizationmentioning
confidence: 99%